Host-guest complex properties of calix[4]arene derivatives: a DFT study of adsorption and sensing of an anticancer drug, 5-fluorouracil - Yüksel, Numan; Fellah, Mehmet Ferdi (Springer Wien, 2021)
In this study, it has been reported the host-guest complex properties of calix[4]arene compounds (the 3rd generation supramolecule) against the 5-fluorouracil (5-FU) anticancer drug by density functional theory calculations at room temperature. The B3LYP hybrid method was used to determine the optimized structures of the host and guest molecules and their complexes. The adsorption energy changes of the complexes formed between calix[4]arene compounds and 5-FU drug were calculated to be negative values. The strongest interaction was determined for the water-soluble calix[4]arene compound with sulfonyl (-SO3H) groups (Delta E = - 98 kJ/mol and Delta H = - 100.5 kJ/mol). Moreover, it was determined that HOMO-LUMO gaps of all calix[4]arene compounds decreased. The charge transfer has occurred between the four calix[4]arene compounds and the drug molecule. The work function values of calix[4]arene compounds have been changed. These results indicate that calix[4]arene derivatives can be used as well-suited 5-FU sensor at room temperature. Solvent effect calculations have stated that the interaction of 5-FU molecule with the calix[4]arene compound with sulfonyl (-SO3H) groups weakens and the Delta E becomes less negative value (- 71.6 kJ/mol). [GRAPHICS] .
FELLAH, Mehmet Ferdi/0000-0001-6314-3365
Keywords: Density functional theory; Calixarenes; Sensors; Adsorption; 5-Fluorouracil